Systematic review of Aboriginal and Torres Strait Islander peoples' experiences and supportive care needs associated with cancer - John Gilroy; Mandy Henningham; Drew Meehan; Farhana Nila; Joanna McGlone; Amanda McAtamney; Kate Whittaker; Bena Brown; Megan Varlow; Tanya Buchanan (BMC, 2024)
Abstract Background Persistent disparities exist between Aboriginal and Torres Strait Islander peoples (the Indigenous peoples of Australia) and non-Indigenous Australians associated with cancer, with Aboriginal and Torres Strait Islander peoples experiencing a longer time to treatment, higher morbidity rates, and higher mortality rates. This systematic review aimed to investigate findings and recommendations in the literature about the experiences and supportive care needs of Aboriginal and Torres Strait Islander peoples with cancer in Australia. Methods A qualitative systematic review was conducted using thematic analysis. Database searches were conducted in CINAHL, Informit, MEDLINE, ProQuest, Scopus, and Web of Science for articles published between January 2000 and December 2021. There were 91 included studies which were appraised using the Mixed Methods Appraisal Tool. The included studies reported on the experiences of cancer and supportive care needs in Aboriginal and Torres Strait Islander populations. Results Six key themes were determined: Culture, family, and community; cancer outcomes; psychological distress; access to health care; cancer education and awareness; and lack of appropriate data. Culture was seen as a potential facilitator to achieving optimal cancer care, with included studies highlighting the need for culturally safe cancer services and the routine collection of Aboriginal and Torres Strait Islander status in healthcare settings. Conclusion Future work should capitalize on these findings by encouraging the integration of culture in healthcare settings to increase treatment completion and provide a positive experience for Aboriginal and Torres Strait Islander peoples with cancer.